Introduction to data compression - Sayood, Khalid (Amsterdam : MK, 2000)
Introduction; Mathematical preliminaries for lossless compression; Huffman coding...
Includes bibliographical references and index.
Keywords: Computers; Data compression (Telecommunication).; Coding theory